Performance of Groundnut (Arachis hypogaea L.) Productivity Through Cluster Front Line Demonstration in Farmer’s Field - Ayyadurai, P.; Shanmugam, P.S.; Sangeetha, M.; Vennila, M.A. (Indian Journal of Extension Education, 2021)
The cluster front line demonstration (CFLD) of groundnut were conducted during kharif season of 2017 and 2018 in 150 farmers holdings of Dharmapuri district, Tamil Nadu to demonstrate the production potential and monitoring returns of best management practices (BMPs). The higher pod yield and drought tolerant variety (TCGS 1043, TMV 14), seed treatment with biofertilizers and bio-fungicides, integrated nutrient management, integrated pest and disease management were demonstrated. The BMPs demonstrated registered mean yield of 18.2 q/ha, which was 31 percent higher than that obtained with farmer’s practice. The incidence of insect pest and disease were lowest in the BMPs compare to FPs. The additional cost of Rs. 4276 to Rs. 6138 gave additional net return ranged from Rs. 11226 to Rs. 17718 per hectare with increased benefit: cost ratio of 1:2.63 to 1:2.89. Data on technology index increased from 21.6 per cent (2017) to 32.8 percent (2018), exhibited response of technology demonstration in this region.
Keywords: Best Management Practices (BMPs); CFLD; Economics; Extension gap; Farmers Practice (FP); Groundnut; Technology gap